'Oil complex' and social responsibility theory of the media: Shaping Nigeria's environmental discourse with social media. (1st June 2014) - Uzoechi, Nwagbara
The aim of this article is to explore how social media can be used to effectively bring behavioural change and rational opinion about 'oil complex' in Nigeria's Niger delta region for a more sustainable future. Second, this article argues that social media can also be used as a medium to shape public opinion, pluralistic views and policy agenda about challenges posed by 'oil complex'. This process resonates with the social responsibility function of the media. While mainstream or traditional media perceptibly steer clear of reporting issues that highly challenge corporate interests, which have strong links with these media outlets, social media can be a platform for critical and balanced reportage of social and environmental issues for diversity of views to be aired. The media's role in this sense will help manage problems associated with 'oil complex' for a more sustainable future in the region.